EVALUASI APAR DAN HIDRAN SEBAGAI UPAYA PENANGGULANGAN KEBAKARAN DI PT X - Mariska Hamid (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2019)
Portable Fire extinguishers and hydrant are tools used for overcoming the fire. The purpose of this research is to learn about fire portable and hydrant application as a defensive action of fire in PT X. This research is a descriptive research with a cross sectional approach. Variable of this research are portable fire extingusher, hydrant and company policy. The result of this research showed  that almost installation of portable fire estingusher is comply with Permenakertans No. 04/PER/MEN/1980 abaout  the requirments of portable fire estingusher, either the hydrant also comply with Kepmen PU No. 02/KPTS/1985 about regulation of preventive and defensive action of fire for bulding , but there is one hydrant which covered by the rest of production materials and there is no white writting or mark "HYDRANT" on some box hydrant. Company is suggested to look at, or aware of the height of portable fire estingusher installation and box hydrant may not covered by anything and give an white writting or mark "HYDRANT'.